MAKNA KEGAGALAN CALEG MENJADI ANGGOTA LEGISLATIF KOTA SEMARANG PERIODE 2009-2014 (Studi Kualitatif Fenomenologis) - Purindawati, Rindang; Indrawati, Endang Sri; Kahija, Y. Franz La (Faculty of Psychology, Diponegoro University, 2010)
Number of candidates who experienced the phenomenon of post-election stress legislature into the background of this research. Changes in the legislative council election system from the system serial number be a majority vote system gives all citizens the opportunity to become representatives in the legislative institution. The opportunity was utilized for each candidate to win the people that are willing to support him in the election, not infrequently they do everything they can to acquire it for example with political money. Efforts are sometimes not in accordance with the results obtained so make candidates be disappointed and even depressed.This qualitative research used a phenomenological approach to existentialism. The subjects were three men who was a former candidate in legislative elections in 2009. Data collection methods using depth interviews, observational methods, recording, and field notes. The result of interview transcripts and analyzed and then made to find psychological meaning, a collection of units of meaning, concept mapping, and the deepest essence of the research.Results from this study that the candidates who failed to become a member of the legislature do not always experience the soul like a lot of shocks reported. Purposes to be a member of the legislative failure is influenced by the interaction of candidates running for the background, experience and expectations developed candidacy. In the face of failure, self-evaluate candidates using the attribution and introspection.Keywords: Caleg, failure of a member of the legislativePermalink :